2019
DOI: 10.1080/15548627.2019.1598752
|View full text |Cite
|
Sign up to set email alerts
|

Regorafenib induces lethal autophagy arrest by stabilizing PSAT1 in glioblastoma

Abstract: GBM (glioblastoma multiforme) is the most common and aggressive brain tumor with no curative options available. Therefore, it is imperative to develop novel potent therapeutic drugs for GBM treatment. Here, we show that regorafenib, an oral multi-kinase inhibitor, exhibits superior therapeutic efficacy over temozolomide, the first-line chemotherapeutic agent for GBM treatment both in vitro and in vivo. Mechanistically, regorafenib directly stabilizes PSAT1 (phosphoserine aminotransferase 1), a critical enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
96
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 109 publications
(105 citation statements)
references
References 61 publications
9
96
0
Order By: Relevance
“…The Fructose-Bisphosphatase 1 (FBP1) is a rate-limiting enzyme in gluconeogenesis, which is suppressed in kidney tumors and thus feeds ccRCC; FBP1 is associated with impaired cell proliferation, glycolysis and the pentose phosphate pathway in ccRCC in a catalytic-activity-independent manner via direct interaction with the HIF inhibitory domain 18 . PSAT1 is up-regulated in many cancers and acts as an oncogene that exerts a vital role in cancer progression and metastasis [19][20][21] . Interestingly, through mining public database and RT-qPCR, we found that PSAT1 in ccRCC patients is down-regulated compared with normal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The Fructose-Bisphosphatase 1 (FBP1) is a rate-limiting enzyme in gluconeogenesis, which is suppressed in kidney tumors and thus feeds ccRCC; FBP1 is associated with impaired cell proliferation, glycolysis and the pentose phosphate pathway in ccRCC in a catalytic-activity-independent manner via direct interaction with the HIF inhibitory domain 18 . PSAT1 is up-regulated in many cancers and acts as an oncogene that exerts a vital role in cancer progression and metastasis [19][20][21] . Interestingly, through mining public database and RT-qPCR, we found that PSAT1 in ccRCC patients is down-regulated compared with normal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we were able to construct four PPI modules, all of which were related to critical GBM biological processes. Highly relevant nodes in the modules, including STAT3, SLC11A1, and ITGAM, have been reported to promote tumor proliferation, angiogenesis, migration, and invasiveness (73)(74)(75)(76)(77). Among the 64 genes validated, 27 (such as ALOX5, CAST, HS6ST1, ITGAM, PTPN6, SLC11A1, and SLC12A7) have been reported to be involved in the pathogenesis of GBM or critical in predicting OS.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have suggested overexpression of PSAT1 protein as a poor prognostic marker in colorectal cancer [17], esophageal squamous cell carcinoma [15], NSCLC [14] and ER(−) breast cancer [16]. However, a recent study suggested that a high level of PSAT1 protein could be a favorable prognostic marker for regorafenib-induced GBM suppression [18]. From literature review and our analyses, we conclude that the prognostic role of PSAT1 overexpression in gliomas, including LGGs and GBM, might be different from that in other cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…However, the prognostic roles of these three genes in LGGs are still unknown. in Glioblastoma with regorafenib treatment [18] NAD+: an oxidized nicotinamide adenine dinucleotide.…”
Section: Phgdh Psph and Psat1 Are Important Regulators Of The Ssp Amentioning
confidence: 99%
See 1 more Smart Citation